2015
DOI: 10.1155/2015/157365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Retinal Nerve Fiber Layer in Retinitis Pigmentosa Using Optic Coherence Tomography

Abstract: Aim. To evaluate the peripapillary retinal nerve fiber layer (RNFL) changes in retinitis pigmentosa (RP) patients using spectral domain optic coherence tomography (Sd-OCT). Methods. We retrospectively examined medical records of forty-four eyes of twenty-two RP patients. The results were also compared with those of previously reported forty-four eyes of twenty-two normal subjects (controls). Records of average and four quadrants peripapillary RNFL thickness measurements using Sd-OCT were assessed. Results. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the RNFL thickness was found to be retained or thickened in the majority of RP patients, and the measurement results are shown in table 2[44,53,54,55,56,57,58]. In addition to the mean RNFL changes [44,55], the quadrants of the RNFL thickening or thinning were different.…”
Section: Retinal Nerve Fiber Layermentioning
confidence: 99%
“…However, the RNFL thickness was found to be retained or thickened in the majority of RP patients, and the measurement results are shown in table 2[44,53,54,55,56,57,58]. In addition to the mean RNFL changes [44,55], the quadrants of the RNFL thickening or thinning were different.…”
Section: Retinal Nerve Fiber Layermentioning
confidence: 99%
“…One explanation could be the topographic distribution of the radial peripapillary capillary plexus (RPPC), which is not noticeable in the temporal sector of the macula compared to the inferior and superior sectors. The RPPC contributes to the SVC together with the superficial capillary plexus (SCP) and is usually preserved in RP as is the thickness of the retinal nerve fiber layers 25,26 . In the 6 × 6-mm OCTA, the SVC density measures globally the www.nature.com/scientificreports/ density of both the SCP and RPPC, hence, the decrease of the SVC density in the superior and inferior sectors could be masked by the normal density of the RPPC.…”
Section: Discussionmentioning
confidence: 99%
“…Walia et al reported RNFL thinning in approximately 40% of RP patients using SD-OCT[25] and Oishi et al reported no signi cant difference between RNFL thickness in normal populations and RP patients using time domain OCT[26]. Yilldirim et al reported that 48% of patients had temporal quadrant RNFL thickening and suggested that glial tissue proliferation, which is secondary to the nerve ber layer atrophy or edema of the remnant RNFL, causes the retinal thickening[27]. These results indicate that RNFL thinning may not be linear and may vary from one stage to another of degeneration.…”
mentioning
confidence: 99%